In a Time-Warp: The Issue of Chronology in Siri Hustvedt’s The Blindfold - Knirsch, Christian (Current Objectives of Postgraduate American Studies, 2012)
The complexities of both the narrative situation and the time structure of Siri Hustvedt’s The Blindfold“ have, so far, been neglected in secondary literature. This essay makes an attempt at restoring the novel’s chronology as far as possible. In a second step, I will then try to interpret the significance of the anachronic way of rendering the plot and deduce certain implications for the novel’s ontology using post-structuralist and postmodernist approaches as well as neurological and astrophysical research findings.